Evaluation of Ergonomic Risks during Dental Work - Petrović V.; Pejčić N.; Bulat P.; Djurić-Jovičić M.; Miljković N.; Marković D. (Balkan Stomatological Society, 2016)
Aim: The purpose was to assess ergonomic risk level in dentistry, which may contribute to manifestation of musculoskeletal disorders (MSD).